Shared Visibilities: An exploration of the client’s use of imagery on the road to UPSR - Davis, Tatiana (European Journal for Qualitative Research in Psychotherapy, 2023)
This article presents findings from research on the interaction between client imagery and Unconditional Personal Self-Regard (UPSR). Through posing the question “What impact does imagery shared within the therapeutic relationship have on UPSR?”, the researcher - herself a person-centred therapist - explores issues emerging from her own experience of the use of imagery language in therapy, both as client and therapist. The research also addresses a lacuna within the literature of person-centred therapy, where little has been written on the potential use of shared language and clients’ choice of imagery. Data from semi-structured interviews with four women trainee person-centred therapists about their experience of using imagery was analyzed using Interpretative Phenomenological Analysis (IPA). The imagery participants used in their own therapy ranged from physical images drawn by them, to images from dreams or inspired by prayer, reflections on the natural world, and visualisations of the self in different imagined contexts. The discussion suggests that client UPSR is indeed impacted by imagery used in the therapeutic relationship, and that the ability of the client to use their own language in therapy to mediate their experience has a positive impact on the therapeutic relationship. This research contributes a new area of thinking to person-centred work, exploring the role of client language in client-led work, and the benefits for therapists of working with and through the images of their clients.